2023
DOI: 10.1039/d2cc06621a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed asymmetric [4+2] annulation of vinyl benzoxazinanones with pyrazolone 4,5-diones to access spirobenzoxazine frameworks

Abstract: A palladium-catalyzed general synthetic strategy to access an attractive and decorated set of spirooxazinane skeletons was successfully achieved using vinyl benzoxazinanone derivatives and ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In order to extend the application of 7 with ketones, Chen et al in 2023 reported the synthesis of chiral spiro derivatives of benzoxazines 27 by enantioselective decarboxylative [4 + 2] palladium catalyzed cycloaddition between 7 and pyrazolone 4,5-diones 26 in moderate to good yields (Scheme 7). [51] Initially, the Pd-stabilized zwitterionic 1,4-dipole XI formed from 7 attacked 26 a and subsequently achieved ring-closure via TS-III instead of TS-IV with steric interaction, furnishing favoured product 27.…”
Section: Palladium Catalyzed [4 + 2] Cycloadditionsmentioning
confidence: 99%
“…In order to extend the application of 7 with ketones, Chen et al in 2023 reported the synthesis of chiral spiro derivatives of benzoxazines 27 by enantioselective decarboxylative [4 + 2] palladium catalyzed cycloaddition between 7 and pyrazolone 4,5-diones 26 in moderate to good yields (Scheme 7). [51] Initially, the Pd-stabilized zwitterionic 1,4-dipole XI formed from 7 attacked 26 a and subsequently achieved ring-closure via TS-III instead of TS-IV with steric interaction, furnishing favoured product 27.…”
Section: Palladium Catalyzed [4 + 2] Cycloadditionsmentioning
confidence: 99%
“…As opposed to alkenes and imines, the carbonoxygen double bond in the ketone suffered from low reactivity and selectivity, which made the reaction of vinyl benzoxazinones with ketones face significant challenge. Consequently, Yang, Huang and co-workers disclosed the first catalytic asymmetric Pd-catalyzed enantioselective decarboxylative [4 + 2] cyclization of vinyl benzoxazinones 1 with ketones 52 (Scheme 17), [32] furnishing a direct and efficient method for constructing the desired chiral spiropyrazolones 53 in moderate yields (55-76% yield) and with excellent enantioselectivities (80-96% ee).…”
Section: Asymmetric [4 + 2] Annulationsmentioning
confidence: 99%
“…1 Recently, considerable efforts have been focused on developing highly efficient and practical methods to construct diverse spiro-pyrazolone frameworks with both structural diversity and complexity. By leveraging versatile building blocks, such as simple pyrazolone, 2 pyrazolone ketimines, 3 pyrazolone 4,5-diones 4 and pyrazolone-derived MBH carbonate substrates, 5 the diverse construction of mono-spirocyclic pyrazolone derivatives has been achieved (Scheme 1B). Compared with other strategies, Pd-catalyzed cycloaddition utilizing zwitterionic π–allyl palladium complexes as key intermediates offers a distinctive pathway in organic synthesis to deliver targeted molecules that are challenging to produce using conventional methods.…”
mentioning
confidence: 99%